PENGORGANISASIAN TENAGA DI USAHA KOVENSI ADIGUNA BORDIR KOTA BENGKULU - Novia Anwari; Wahiruddin Wadin; Parlan Parlan (UNIB Press, Universitas Bengkulu, 2019)
Organizing is a management activity carried out to regulate all the necessary resources intended to be human elements so that the execution and execution of tasks can be completed with success. Humans are the most important element through organizing they can carry out their duties.In this study researchers used qualitative methods with results 1. Organizing Planned in the Adiguna Embroidery Convection business in the recipients of employees received here are those who want to work hard and discipline with time. 2. divide up the work of Mr. Suyono to distribute the work to employees even though the results obtained every day employees with each other are different but the work is done well. 3. Classify Activities into Practical Units with the provision of modern means of making the work practical so that the work done is more efficient and effective can be done well, on time and the results are neater. 4. Determining the obligations that must be performed by the employee to provide adequate means of equipment and physical space that the employee needs to do is work according to the field of work position. the room and facilities as a means of supporting the production process are adequate and the material provided by Mr. Suyono is commensurate with the amount done even more 5. The assignment of personnel who are capable of working on the production process of clothing is good even though there is no special training for employees in Adiguna Embroidery Convection business 6. Delegation of authority within the Adiguna Convection Embroidery organizational structure in the form of a line based on orders and supervision in one hand. Keywords: organizing, labor